A pictorial key to differentiate the recently detected exotic Haemaphysalis longicornis Neumann, 1901 (Acari, Ixodidae) from native congeners in North America - Egizi, Andrea M.; Robbins, Richard G.; Beati, Lorenza; Nava, Santiago; Evans, Colleen R.; Occi, James L.; Fonseca, Dina M. (Pensoft Publishers, 2019)
Until recently, only two haemaphysaline species, Haemaphysalis chordeilis (Packard, 1869) and Haemaphysalis leporispalustris (Packard, 1869), were known to occur in the United States, and neither was considered to be of significant medical or veterinary importance. In 2017–2018 established populations of the Asian longhorned tick, Haemaphysalis longicornis Neumann, 1901, were detected in the eastern US for the first time. Haemaphysalis longicornis has the potential to be a significant threat to human and animal health, and the urgent need to determine the full extent of its distribution and host range requires availability of a straightforward and practical guide to differentiate it from native species. We created a pictorial dichotomous key to all stages of Haemaphysalis spp. known to occur in North America with scanning electron photomicrographs of all H. longicornis life stages, including rarely seen males, to aid researchers in differentiating these species. The largely Neotropical species Haemaphysalis juxtakochi Cooley, 1946, with established populations in Mexico and sporadic detections in the US on migrating birds is also included.